Technology's Role to Avoid the Spread of COVID-19 - Meiryani; Siagian, Pariang; Lusianah; Lesmana, Theresia (International Journal of Psychosocial Rehabilitation, 2020)
The world and Indonesia are currently focusing on counteracting the widespread corona virus. In an effort to minimize the impact, several countries have utilized application technology. Video call services such as FaceTime have also helped with virtual doctor visits or telemedicine, so patients can consult with doctors online and avoid hospital visits. Streaming movies also benefit because people choose home entertainment rather than going to public spaces. With the internet the public can keep abreast of the latest news about Covid-19 and not get caught up in hoax news or misinformation.